2021
DOI: 10.3390/ijerph18157737
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Exposure by Spraying Activities—Status and Future Needs

Abstract: Spray applications enable a uniform distribution of substances on surfaces in a highly efficient manner, and thus can be found at workplaces as well as in consumer environments. A systematic literature review on modelling exposure by spraying activities has been conducted and status and further needs have been discussed with experts at a symposium. This review summarizes the current knowledge about models and their level of conservatism and accuracy. We found that extraction of relevant information on model pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…This is a result of the comparatively low cutoff of 10 Pa for the assumption of complete instantaneous release. Other authors have also indicated the conservative nature of the inhalation algorithm [7,13] Dermal route. The dermal algorithm is:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a result of the comparatively low cutoff of 10 Pa for the assumption of complete instantaneous release. Other authors have also indicated the conservative nature of the inhalation algorithm [7,13] Dermal route. The dermal algorithm is:…”
Section: Resultsmentioning
confidence: 99%
“…This effort is not intended to be a statistical assessment of TRA tool performance (indeed one of the findings of this and other studies is that consumer exposure data needed for exposure model evaluation are generally sparse [ 6 , 13 ]), but rather to consider the published findings of other tool users and also the results of recent studies specifically designed to address REACH exposure information requirements. Since the release of TRA, several downstream user sectors have published Specific Consumer Exposure Determinants (SCEDs) of values meant to be used to refine the TRA input parameters for specific scenarios when appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Size of the aerosols in turn depends on the spraying device and many other factors, such as size reduction of droplets due to evaporation of volatile components, containment and spraying nozzle. In practice, accurate information on these parameters is often not available, because well documented spray exposure measurements are scarce [ 25 ]. Further research is required on new modelling approaches such as relative source strength [ 26 ], harmonisation between models regarding input parameters and identification of standard spray scenarios.…”
Section: Resultsmentioning
confidence: 99%
“…Given the large number and variety of chemical substances present in spray products and the variability in use patterns, it is not possible to measure all potential exposures in different workplaces, but exposure modelling is imperative as well. This need has been met by the development of a variety of exposure models in research and regulatory communities [ 7 ]. Lists of models using different specific approaches to estimate exposure are also given in the BPR and REACH guidance [ 8 , 9 ] and by Hahn et al [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This need has been met by the development of a variety of exposure models in research and regulatory communities [ 7 ]. Lists of models using different specific approaches to estimate exposure are also given in the BPR and REACH guidance [ 8 , 9 ] and by Hahn et al [ 7 ]. These models are designed for different applications and different tiers of exposure assessment (i.e., screening to higher tiers), where a distinction is made between two sources of exposure: (1) primary exposure from the spray cloud and its overspray; (2) secondary exposure caused by the evaporation of substances from the treated surfaces.…”
Section: Introductionmentioning
confidence: 99%